Production of herbal shampoo from Madagascar periwinkle - Senin, Hj. Zulkifli; Ayob, Muhammad Raimi; Shamsuddin, Muhammad Syahmi Al Naqim; Azman, Muhammad Zuhairi (Penerbit UTHM, 2020)
Recently, the society interest in using herbal shampoos has increased significantly. Big companies have started to produce herbal shampoo to meet the market demands. However, most of these shampoos contain chemicals that could be harmful to human health. The main purpose of this study are to produce homemade herbal shampoo from Madagascar Periwinkle plant without harmful chemicals and have additional benefits to consumers. By using stem and leaf extract from the plant and cold press machine, we analysed the quantitative aspect of the extracts and use it as a main ingredient to produce homemade herbal shampoo. The extracts are then used as ingredients in production of the shampoo. Several tests were conducted to determine the performance of the shampoos. The Fourier Transform Infrared Spectroscopy (FTIR) analysis shows presence oh -OH groups and C=O bond to indicate the presence of vinca alkaloids. The performance tests result inconsistent to one extract only. This study provided an information to future researchers regarding the study of Madagascar Periwinkle and effectiveness of this plant in herbal shampoos production.